The Efficacy of Tumor Characterization for Colorectal Lesions with Blue Light Imaging of a Compact Light-Emitting Diode Endoscopic System Compared to a Laser Endoscopic System: A Pilot Study. (12th April 2022) - Inoue, Ken; Yoshida, Naohisa; Kobayashi, Reo; Tomita, Yuri; Hashimoto, Hikaru; Sugino, Satoshi; Hirose, Ryohei; Dohi, Osamu; Yasuda, Hiroaki; Yasuda, Ritsu; Murakami, Takaaki; Inada, Yutaka; et al.
Abstract : Background : A compact and cost-effective light source-processor combined 3-color light-emitting diode (LED) endoscopic system (ELUXEO-Lite: EP-6000, Fujifilm Co., Tokyo) with a magnified colonoscope (EC-6600ZP, Fujifilm Co.) has been released. Aims : In this study, we analyzed the efficacy of this system for colorectal tumor characterization with magnified blue light imaging (BLI-LED) and image's subjective and objective evaluations, compared to a magnified blue laser imaging (BLI-LASER) using a standard LASER endoscopic system. Methods : We retrospectively reviewed 37 lesions observed with both BLI-LED and BLI-LASER systems from 2019 using the Japanese narrow band imaging classification. Two representative magnified images, one BLI-LED and one BLI-LASER, of the same area of a lesion were evaluated for diagnostic accuracy and visualization quality by three experts and three non-experts. Their color difference values (CDVs) and brightness values (BVs) were also calculated as objective indicators. Results : Among 37 lesions, mean tumor size was 18.9 ± 13.1 mm, and 21 lesions were nonpolypoid. Histopathology revealed 14 sessile serrated lesions, 7 adenomas, 12 high-grade dysplasias and T1a cancers, and 4 T1b cancers. The diagnostic accuracy rates of BLI-LED/BLI-LASER of experts and non-experts were 90.1% and 87.4% (p = 0.52 ) and 89.2% and 89.2% (p = 0.99 ). The percentages of instances where BLI-LED images were better, the two imaging types were equivalent, or BLI-LASER images were better were 16%/83%/1% for experts and 19%/58%/23% for non-experts (p < 0.001 ). CDVs and BVs between BLI-LED and BLI-LASER were not significantly different (CDVs: p = 0.653, BVs: p = 0.518 ). Conclusions : BLI-LED using the compact system was noninferior to BLI-LASER for colorectal tumor characterization and image quality.